Estudo de alguns aspectos do ácido desoxirribonucleico (DNA) e mecânica quântica supersimétrica - Drigo Filho, Elso [UNESP] (Universidade Estadual Paulista (Unesp), 1992)
We study the thermic denaturation and some low frequency oscillations In DMA molecule. An important point of our approach is lhe potential which we use to simulate the Hydrogenbond. For thls prupose we suggest a new potentia, that is obtained by the formalism of the supersyminetric quantum mechanics.The results obtained by us are compared with results obtained from other potentials and with experimental data. On the other hand, we use the super algebra to indicate a method to generalize quantum potentials and to determine new exactaly sovable potentials. We also show how to solve the Schrôdinger equation throught supersymmetry
Keywords: Teoria quântica; DNA; Supersimetria